2012
DOI: 10.1021/ct300701m
|View full text |Cite
|
Sign up to set email alerts
|

Toward the Quantum Chemical Calculation of NMR Chemical Shifts of Proteins. 3. Conformational Sampling and Explicit Solvents Model

Abstract: Fragment-based quantum chemical calculations are able to accurately calculate NMR chemical shifts even for very large molecules like proteins. But even with systematic optimization of the level of theory and basis sets as well as the use of implicit solvents models, some nuclei like polar protons and nitrogens suffer from poor predictions. Two properties of the real system, strongly influencing the experimental chemical shifts but almost always neglected in the calculations, will be discussed here in great det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
134
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(151 citation statements)
references
References 85 publications
17
134
0
Order By: Relevance
“…These accuracies are very similar to DFT-based predictions made by other researchers (e.g. (Zhu et al, 2012), (Zhu et al, 2013), (Exner et al, 2012)) as well as CheShift-2 (Martin et al, 2013), which is another DFT-based chemical shift predictor for Cα and Cβ atoms. The RMSD values computed using ProCS15 for Ubiquitin can be reduced by as much as 0.7, 0.1, and 0.5 ppm for carbon, hydrogen, and nitrogen by using NMR-derived structural ensembles.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…These accuracies are very similar to DFT-based predictions made by other researchers (e.g. (Zhu et al, 2012), (Zhu et al, 2013), (Exner et al, 2012)) as well as CheShift-2 (Martin et al, 2013), which is another DFT-based chemical shift predictor for Cα and Cβ atoms. The RMSD values computed using ProCS15 for Ubiquitin can be reduced by as much as 0.7, 0.1, and 0.5 ppm for carbon, hydrogen, and nitrogen by using NMR-derived structural ensembles.…”
Section: Discussionsupporting
confidence: 87%
“…For example, Zhu, He and Zhang (Zhu et al, 2012) used B3LYP/6-31G(d,p) to compute hydrogen and carbon chemical shifts for small proteins that correlate well with experimental measurements with r values typically ≥ 0.98 when solvent effects are taken into account. Exner, Möller, and co-workers (Exner et al, 2012) have obtained similar results using B3LYP/6-31G(d) and even observed a correlation of 0.81 for the notoriously difficult amide N by averaging over several snapshots. Finally, Vila, Baldoni and Scheraga (Vila et al, 2009b) on Cα chemical shifts in Ubiquitin and found very little difference in performance with all r and RMSD values in the range 0.902 -0.908 and 2.12 -2.30 ppm.…”
Section: Resultssupporting
confidence: 55%
See 2 more Smart Citations
“…For reliable comparisons of NMR chemical shifts, it is important to consider the influence of explicit solvent molecules and counterions. 123125 In this work, solvated configurations were sampled by using NPT explicit solvent molecular dynamics (see Computational Details). After equilibration, snapshots were randomly sampled from a 2 ns trajectory, including all water molecules and counterions within 20 Å of the center of the guanine quadruplex.…”
Section: Resultsmentioning
confidence: 99%